Two-photon absorption based detection in semiconductor microcavities - O'Dowd, John (Trinity College (Dublin, Ireland). School of Physics, 2009)
The most important feature of a two-photon absorption microcavity (TPAM) is that of its enhancement of the optical field which enhances the level of twophoton absorption (TPA) for a particular input optical power incident on the detector. The TPAM is shown to not only enhance the level of TPA but also to suppress the level of residual single photon absorption (SPA) relative to the level of TPA. This allows a TPA dominated signal to be accessed at much lower incident optical powers than would be possible for a similar GaAs absorbing region which was not sandwiched between two highly reflective distributed Bragg retlectors (DBR's). The TPA coefficient is estimated to be approximately 15 cm/GW at 1560 nm in (001) GaAs. The residual SPA coefficient in the unintentionally doped GaAs active layer of the TPAM (which is grown by metalorganic chemical vapour deposition) is approximately 1.0 x 10 -4 cm -1.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.